Social Media Influencer Engagement and Mental Health Outcomes: The Moderating Analysis of Family Income Differences - Lajan Mohammed Othman (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2026)
The rapid proliferation of social media platforms has significantly altered the manner in which people receive information, define their identities, and assess their self-perceptions, giving rise to new psychological challenges. Drawing on Social Comparison Theory, Role Theory, and Consumer Socialization literature, this study proposes that frequent engagement with social media influencers negatively affects psychological well-being by triggering upward social comparison, material pressure, and feelings of inadequacy. The research further examines whether family income moderates the strength of this relationship. It is hypothesized that low- and middle-income individuals experience more harmful outcomes because they may lack the means to replicate the promoted lifestyles. This study employed a cross-sectional, quantitative approach, collecting data from 165 participants in Erbil, Kurdistan, Iraq between October 2025 through December 15, 2025. A Structural Equation Model was used to analyze these relationships. The findings confirm that engagement with social media influencers is a significant negative predictor of psychological well-being. Moreover, family income is a significant moderator, such that low and medium income enhance the negative impact, while high income attenuates it. This study contributes to the literature on digital well-being by emphasizing the importance of socioeconomic context.